Shoulder flexibility and strength in elite girl tennis players with and without history of shoulder pain - Gillet, B.; Sevrez, V.; Diger, M.; Berger-Vachon, C.; Rogowski, I. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study aimed at comparing the glenohumeral (GH) range of motion, and shoulder and scapular muscle strength in elite girl tennis players with (group HoSP; n=15) and without (group H; n=16) history of shoulder pain. The GH joint range of motion in internal (IROM) and external rotation (EROM), as well as the maximal isometric strength of eight shoulder and scapular muscles were bilaterally assessed in 31 girl players. The results showed an increased IROM in HoSP, suggesting a laxity, which may contribute to humeral translation motions in the glenoid cavity at critical tennis positions. The HoSP group also presented a weakness in serratus anterior muscle strength, which may create improper motions of the scapula during the tennis strokes. These findings suggested that stretching and strengthening rehabilitative programs may be specifically developed for the young girl athletes involved in an intensive overhead activity practice.